The Invisible Veterans from the Iraq Wars and What Educational Theories May Benefit the Sisterhood Population - Jessica Dunn (Adult Education Research Conference, 2024)
Women are now a critical resource for military recruitment after their involvement in combat in the Iraq Wars, yet little research has been done on this growing Sisterhood population.
Keywords: Women Veteran; Invisible; Sisterhood; Iraq